Clinical Spectrum of Pseudotumor Cerebri - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Erciyes University, Kayseri, Turkey, studied the etiological and clinical features, treatment, and prognosis of pseudotumor cerebri (PTC) in 42 consecutive patients (average age at symptom onset 10 years; range 12 months to 17 years).